QUANTILE REGRESSION OF GERMAN STANDARD FARMLAND VALUES: DO THE IMPACTS OF DETERMINANTS VARY ACROSS THE CONDITIONAL DISTRIBUTION?. (2nd May 2018) - LEHN, FRIEDERIKE; BAHRS, ENNO
Abstract: Because of considerably increased farmland prices, not only in Germany, the question arises whether farmland is still affordable for farmers. Hence, there is a call for price caps. If farmland prices are to be capped by political intervention, identifying the main farmland price determinants especially for the highest prices is essential. Using quantile regression for German standard farmland values, we find heterogeneous relationships across the estimated quantiles for several covariates. Nonagricultural factors are often more pronounced at the upper tail of the conditional distribution. We recommend focusing primarily on factors in the upper quantiles to prevent further farmland price increases.